2021
DOI: 10.47067/reads.v7i4.406
|View full text |Cite
|
Sign up to set email alerts
|

Can Financial Development Help in Raising Sustainable Economic Growth and Reduce Environmental Pollution in Pakistan? Evidence from Non Linear ARDL Model

Abstract: It is a global challenge to reduce environmental pollution and enhance sustainable economic growth.  This study explores the role of financial development as an instrument in reducing environmental pollution and enhancing sustainable economic development in Pakistan for the period 1980-2020. The Non-linear Autoregressive Distributed Lag (NARDL) econometrics technique has been utilized to find the association between environmental pollution, economic growth, and financial development. The results show that posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It can be observed that all mean values of variables are higher than their standard deviation. This indicates that all the data are under dispersed (Amjad et al 2021 ). Based on the normality test, LNGDPPC, CO 2 , LNLFTOT, LNEDU, and LNINDU are not normal at the 5% level.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It can be observed that all mean values of variables are higher than their standard deviation. This indicates that all the data are under dispersed (Amjad et al 2021 ). Based on the normality test, LNGDPPC, CO 2 , LNLFTOT, LNEDU, and LNINDU are not normal at the 5% level.…”
Section: Resultsmentioning
confidence: 97%
“…Asteriou and Spanos ( 2019 ) found that FD increases economic growth in 26 European countries before the financial crisis, while after the financial crisis, it declines economic growth. Amjad et al ( 2021 ) examined the impact of FD on economic growth and the environment from 1990 to 2020 in Pakistan. The Nonlinear ARDL econometrics technique was employed to determine the empirical results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level and quadratic coefficients of the FD index propose a U-shaped relationship (Rani et al 2022a , 2022b ), which means that a higher level of FD in SAARC countries degrades CO2. The moderator variable KOF improves the environmental quality and decreases the CO 2 emissions in Q 2 and Q 3 (Amjad et al 2021b ; Sun et al 2021 ; Rahman, 2020 ). However, Guan et al ( 2022 ) found that KOF decreases CO 2 emissions.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve higher economic growth, most of the economies rely on fossil fuel consumption by the massive industrialization (Abad-Segura et al 2020 ; Hsu et al 2021 ). It badly pollutes the environmental quality which causes global warming, flooding, melting ice caps, and climate vulnerability (Amjad et al 2021b ). The most recent conference on climate change COP26 paid special attention to decline greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%
“…Using Cobb-Douglas production function in empirical analysis the study showed that labor force participation is an important component of EG. Amjad et al (2021) pointed out that urban population insignificantly increases EG in Pakistan. The most recent study by Wang et al (2022) showed that labor force participation significantly escalates EG in BRICS countries.…”
Section: Literature Reviewmentioning
confidence: 99%